1979
DOI: 10.1002/ijc.2910230107
|View full text |Cite
|
Sign up to set email alerts
|

14q+ marker chromosome in an EBV‐genome‐negative lymph node without signs of malignancy in a patient with EBV‐genome‐positive nasopharyngeal carcinoma

Abstract: In a patient with an EBV-genome-positive nasopharyngeal carcinoma, an EBV-genome-negative inguinal lymph node without histological evidence of malignant lymphoma or metastatic carcinoma growth was found to contain a 14q+ marker chromosome, identified as an 8;14 translocation, in all cells analyzed. This observation indicates that chromosome aberrations may precede histological signs of malignancy. The possible implication of this finding in relation to the postulated role of the 14q+ marker and lymphoma develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…There is a close association of Epstein-Barr virus (EBV) with Burkitt's lymphoma (BL), and also with undiffxentiated nasopharyngeal carcinoma (NPC) (ref. in Klein, 1979). About 97% of BL arising in the highly endemic regions of Africa, and 100% of NPC tested, irrespective of geographic location, are monoclonal proliferations of EBV-carrying cell clones, i. e. the tumor cells carry multiple copies of the EBV genome and regularly express the EBV-determined nuclear antigen, EBNA.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…There is a close association of Epstein-Barr virus (EBV) with Burkitt's lymphoma (BL), and also with undiffxentiated nasopharyngeal carcinoma (NPC) (ref. in Klein, 1979). About 97% of BL arising in the highly endemic regions of Africa, and 100% of NPC tested, irrespective of geographic location, are monoclonal proliferations of EBV-carrying cell clones, i. e. the tumor cells carry multiple copies of the EBV genome and regularly express the EBV-determined nuclear antigen, EBNA.…”
mentioning
confidence: 90%
“…It has been suggested that African BL develops in several steps: EBV-induced immortalization of normal diploid B-lymphocytes followed by appearance of the specific translocation which leads to an autonomously growing monoclonal tumor (Klein, 1979). It would therefore be of great interest to examine whether the other EBV-carrying neoplasm, NPC, also shows a specific chromosome change.…”
mentioning
confidence: 99%
“…'~ They assumed that the metastatic tumor cells were responsible for the chromosome alterations. Thus far in BL, the t(8; 14) has only been demonstrated once in tissue that histologically did not appear to be involved with tumor. ' Mitelman and associates reported a patient with Epstein-Barr Virus (EBV)-genome positive, nasopharyngeal carcinoma in whom an inguinal node histologically demonstrated nonspecific, reactive lymphadenitis and was EBV-genome negative although positive for the t(8; 14).14 It was hypothesized that this may, in fact, represent a prelymphomatous state and that the chromosomal changes occur before there is histologic evidence of tumor involvement.…”
Section: Discussionmentioning
confidence: 99%
“…8 and No. 14 [t(8;14)] was first recognized in tumor cells from patients with Burkitt's lymphoma (BL) in 1976.' It has been identified in both endemic and non-endemic forms.'…”
mentioning
confidence: 99%